The Challenge of Leadership Accountability for Integrity Capacity as a Strategic Asset - Petrick, Joseph A. (Journal of business ethics, 2001)
The authors identify the challenge of holding contemporary business leaders accountable for enhancing the intangible strategic asset of integrity capacity in organizations. After defining integrity capacity and framing it as part of a strategic resource model of sustainable global competitive advantage, the stakeholder costs of integrity capacity neglect are delineated. To address this neglect issue, the authors focus on the cultivation of judgment integrity to handle behavioral, moral and hypothesized economic complexities as key dimensions of integrity capacity. Finally, the authors recommend two leadership practices to build competence in business leaders to enhance integrity capacity as an organizational strategic asset.